Efficacy and safety of prucalopride in patients with chronic idiopathic constipation stratified by age, body mass index, and renal function: a post hoc analysis of phase III and IV, randomized, placebo-controlled clinical studies - Anthony Lembo; Kyle Staller; Mena Boules; Paul Feuerstadt; William Spalding; André Gabriel; Ashraf Youssef; Yunlong Xie; Brian Terreri; Brooks D. Cash (Therapeutic Advances in Gastroenterology)
Background: Prucalopride (1 or 2 mg once daily) is approved for treating adults with chronic idiopathic constipation (CIC). Objectives: We determined the effect of age, body mass index (BMI), and renal function on the efficacy and safety of prucalopride in adults with CIC. Design: Data were pooled from six 12-week, phase III–IV clinical studies in adults who received prucalopride (1 or 2 mg once daily) or placebo for CIC. Methods: Adults were stratified by age (<50; 50–64; ⩾65 years), BMI (underweight/healthy weight, <25 kg/m 2 ; overweight, 25 to <30 kg/m 2 ; obese, ⩾30 kg/m 2 ), and renal function (normal renal function, estimated glomerular filtration rate (eGFR) ⩾90 mL/min/1.73 m 2 ; mild renal impairment, eGFR 60 to <90 mL/min/1.73 m 2 ; moderate renal impairment, eGFR 30 to <60 mL/min/1.73 m 2 ). The primary efficacy endpoint was the proportion of patients with a mean of ⩾3 complete spontaneous bowel movements/week over 12 weeks. Safety data were evaluated descriptively. Results: Of 2484 patients stratified by age (prucalopride, n  = 1237; placebo, n  = 1247), 1402, 708, and 374 were aged <50, 50–64, and ⩾65 years, respectively. Of 2482 patients stratified by BMI (prucalopride, n  = 1237; placebo, n  = 1245), 1425, 713, and 344 were underweight/healthy weight, overweight, and obese, respectively. Of 2474 patients stratified by renal function (prucalopride, n  = 1233; placebo, n  = 1241), 1444, 869, and 161 had normal renal function, mild renal impairment, and moderate renal impairment, respectively. More prucalopride-treated than placebo-treated patients achieved the primary efficacy endpoint. The difference was significant for all subgroups, except for the obese and moderate renal impairment subgroups. More prucalopride-treated than placebo-treated patients reported treatment-related adverse events in most subgroups. Conclusion: Prucalopride demonstrated efficacy in adults with CIC, irrespective of age, BMI, and renal function. No unexpected safety concerns were identified. Trial registration: ClinicalTrials.gov identifiers ( https://clinicaltrials.gov/ ): NCT01147926, NCT01424228, NCT01116206, NCT00483886, NCT00485940, NCT00488137.